James and the Giant Peach - Dahl, Roald; Illustrated by Blake, Quentin (London Puffin Books, 2016)
James Henry Trotter lives with two ghastly hags. Aunt Sponge is enormously fat with a face that looks boiled and Aunt Spiker is bony and screeching. He's very lonely until one day something peculiar happens. At the end of the garden a peach starts to grow and Grow and Grow.
Include Illustrations
Keywords: Fairy tales